An Interview with Jeanne Gang - Corbin Keech; Jeanne Gang (Oz, 2016)
Corbin Keech is an architect at Studio Gang and an alumnus of Kansas State University. Here, he questions the concept of innovation in architecture through the lens of the studio’s work, in conversation with founding principal Jeanne Gang.